Do final-year medical students in Scotland have the knowledge and confidence to deliver the physical activity guidelines? A cross-sectional online survey to evaluate changes over a decade - Gemma C Ryde; Isabelle Schlegel (BMJ Open)
Objectives This study assessed knowledge of physical activity (PA) guidelines and confidence to deliver PA advice, across current final-year medical students in Scotland. This follows a 2013 survey finding that this cohort lacked this knowledge and confidence; thus, authors recommended improvements to undergraduate medical PA education and re-evaluation of these measures thereafter.Design A cross-sectional online survey.Setting The survey was distributed across four Scottish universities.Participants Final-year undergraduate medical students; n=166 completed the survey. 69% women, 23.3±1.8 years old and 69% met the PA guidelines.Results 27% correctly identified the UK PA guidelines, despite 52% stating awareness of these. While 80% reported receiving PA education, only 20% felt adequately trained to give PA advice to the general population. This study highlights that compared with 2013, more students were aware of PA guidelines and had received training, but fewer could identify the guidelines, and they felt less adequately trained to give PA advice.Conclusion This study highlights the ongoing need to improve PA in the undergraduate medical curriculum. Future studies should continue to evaluate students' confidence and ability to deliver PA advice to patients as PA training is implemented across UK universities.